Pengaruh Residu Mulsa Jerami Padi dan Pupuk Organik Plus terhadap Produksi Tanaman Jagung Pulut (Zea mays ceratina Kulesh) - La Ode Afa; Akmal Akmal; La Karimuna; La Ode Safuan (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
The use of organic matter, which has a long-term impact, increases soil fertility because it contains residue. The research examines how rice straw mulch and organic fertilizer residue affect glutinous corn yield. This study was carried out at the Faculty of Agriculture Field Laboratory, Halu Oleo University, from May to August 2022. This Experiment used a randomized block design with a split plot design. The main plot, i.e. residue of rice straw mulch (M): without the residue of rice straw mulch (M0), the residue of rice straw mulch 4 t ha-1 (M1), and 8 t ha-1 (M2). Subplot, i.e. residue of plus organic fertilizer (P): without the residue of plus organic fertilizer (P0), a residue of plus organic fertilizer 2,5 t ha-1 (P1), 5 t ha-1 (P2), and 7,5 t ha-1 (P3). The length of the cob measured without husk, fresh weight of the cob with husk and without husk, dry weight of the cob without husk, number of seeds per cob, seed weight per cob, the weight of 100 seeds, and yield. After conducting an ANOVA analysis of the data, proceed with DMRT at a significant level of 95% if the analysis yields a significant effect (Fhit> Ftab). The research results showed that rice straw mulch plus organic fertilizer residue significantly affected yield components and yield. The residue of rice straw mulch 8 t ha-1 (M2) and deposition of plus organic fertilizer 7,5 t ha-1 (P3) produce the highest glutinous corn yield, i.e. 2,38 t ha-1 and 2,34 t ha-1 or increasing 92% and 75% compared without treatment. For efficiency of costs and realizing sustainable agriculture, it is necessary to utilize residues of organic material in the cultivation of food crops.